Odpowiedzi

Najlepsza Odpowiedź!
2010-02-08T18:31:10+01:00
A)3x+y=5
2x-y=0
5x=5 |:5
x=1
3+y=5
y=2
e)
-2x+y=0 |×3
3x-3y=1

-6x+3y=0
3x+3y=1
-3x=1 |:(-3)
x=-⅓
⅔+y=o
y=-⅔
1 5 1
2010-02-08T18:33:03+01:00
A){3x+y=5
{2x-y=0

3x + y -2x - y = 5 + 0
3x -2x = 5
x= 5

2x-y=5
2 * 5 - y= 0
10 -y=0
10= y

{x= 5
{y= 10

e){-2x+y=0| *3
{3x-3y=1

{-6x + 3y = 0
{3x-3y=1

-6x + 3y + 3x -3y= 0 +1
-3x= 1 | : (-3)
x = -1/3

-2x + y= 0
-2 * (-1/3) +y =0
2/3 + y =0
y= -2/3

{x=-1/3
{y= - 2/3
1 4 1
2010-02-08T18:37:11+01:00
A){3x+y=5/*2
{2x-y=0/*(-3)

{6x+2y=10
{-6x+3y=0
_____________
5y=10/5
y=2
x1



b){-2x+y=0/*6
{3x-3y=1/*4

{-12x+6y=0
{12x-12y=4

-6y=4
y=(-0.(6666666666666666666666666666666666666667)

3x-0.6666666666666666666666666666666666666667*3=1
3x-2=1/+2
3x=3/ /3
x=1

x=1
y=0.6666666666666666666666666666666666666667
Sprawdzenie:3-(0.6666666666666666666666666666666666666667*3)=1